Optimal line current limitation of CPLs fed through input LC-filters. (August 2019) - Mosskull, Henrik; Jansson, Magnus; Trostén, Torbjörn
Abstract: Active stabilization of a constant power load (CPL) fed through an input LC filter fundamentally limits achievable performance of power control. This restriction is here explicitly shown to also apply to dynamic performance of so-called line current limitation, functionality regulated for traction systems by European standards. Subject to system stability, achievable control performance is explored, and is shown to roughly be reached with simple first-order low-pass filter controllers, added on top of basic stabilization. Depending on actual limitation realization and the available control inputs, it is shown that additional restrictions may apply. Derived results are verified through accurate non-linear simulations.